Fostering Development in Midlife and Older Age: a Positive Psychology Perspective - Crăciun, Irina Catrinel (Springer International Publishing AG, 2023)
This handbook integrates and discusses a growing evidence base concerning individual development across middle and late adulthood. The book includes a comprehensive analysis of what growth implies within midlife and older age and considers how different developmental areas are intertwined (i.e., physical, cognitive, social and emotional development as well as personality growth). As the gap between theory and practice still constitutes an issue in developmental research, the handbook also aims to provide illustrative examples of prevention and intervention from a positive psychology perspective. These were selected to represent a variety of topics, relevant for individual development where research informs practice, ranging from happiness, grandparenthood, love and sexuality to loneliness, depression, anxiety, suicide prevention and coping with death.This handbook is a must-have resource for students and researchers working in developmental psychology, health psychology, gerontology and, public health. It will also be of interest to practitioners such as counsellors, life coaches, psychotherapists, organizational psychologists, health professionals, social workers or public health planners